2014
DOI: 10.1016/j.ijgo.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy following second‐ or third‐trimester intrauterine fetal death

Abstract: Most pregnancies after IUFD resulted in a live birth; however, adverse obstetric outcomes were more common when the previous stillbirth was due to placental causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, the gestational age at fetal death likely has greater etiologic and prognostic significance; studies show that the risk of fetal death is affected by the gestational age at which fetal death occurred in the previous pregnancy. 8 The singular emphasis placed on gestational age at stillbirth in vital records and perinatal registries represents an anachronism and reflects an era when it was not possible to accurately identify the time of fetal death. Increasing the emphasis on documenting the timing of fetal death may also reduce the frequency of "false stillbirths" 4 (ie, early neonatal deaths erroneously labeled stillbirths), a contemporary problem among near-viable live births that tends to reduce neonatal mortality rates and increase fetal death rates.…”
Section: The Clinical Significance Of Fetal Death Compared With Stillmentioning
confidence: 99%
“…However, the gestational age at fetal death likely has greater etiologic and prognostic significance; studies show that the risk of fetal death is affected by the gestational age at which fetal death occurred in the previous pregnancy. 8 The singular emphasis placed on gestational age at stillbirth in vital records and perinatal registries represents an anachronism and reflects an era when it was not possible to accurately identify the time of fetal death. Increasing the emphasis on documenting the timing of fetal death may also reduce the frequency of "false stillbirths" 4 (ie, early neonatal deaths erroneously labeled stillbirths), a contemporary problem among near-viable live births that tends to reduce neonatal mortality rates and increase fetal death rates.…”
Section: The Clinical Significance Of Fetal Death Compared With Stillmentioning
confidence: 99%
“…Pregnancy loss rises with the occurrence of previous miscarriages; and pregnancy after one, two, three or four miscarriages is likely to fail in 16%, 25%, 45%, and 54% of women, respectively . In addition, pregnancies with prior miscarriages seem to have higher possibility of complications, such as vaginal bleeding, preterm delivery, placental abruption, and cesarean section, compared to pregnancies without these histories . In the USA, the pregnancy loss rate decreased by 8% between 1996 and 2003, but has stayed higher than rates in many northern and western European countries.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, pregnancies with prior miscarriages seem to have higher possibility of complications, such as vaginal bleeding, preterm delivery, placental abruption, and cesarean section, compared to pregnancies without these histories. 8,9 In the USA, the pregnancy loss rate decreased by 8% between 1996 and 2003, but has stayed higher than rates in many northern and western European countries. The official rate of pregnancy loss showed a decline by 21% during the 7-year period in China, which accounted for one-third of the world's legal abortions in 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Paternal smoking 4half a pack per day yielded the greatest odds ratio among the three significant environmental factors, reemphasizing the importance of this risk factor for congenital anomalies according to previous studies. [28][29][30] Several studies have indicated that previous miscarriage could indicate a higher risk for poor outcomes in subsequent pregnancies, [31][32][33] especially those due to placental causes. 33 This might be related to a higher possibility of placental inflammation for pregnant woman with a history of pregnancy loss, 34 which may also trigger a fetal inflammatory response and vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Several studies have indicated that previous miscarriage could indicate a higher risk for poor outcomes in subsequent pregnancies, [31][32][33] especially those due to placental causes. 33 This might be related to a higher possibility of placental inflammation for pregnant woman with a history of pregnancy loss, 34 which may also trigger a fetal inflammatory response and vasculopathy. 35 Maternal common cold and smoke exposure during pregnancy are also possibly linked with fetal inflammation and abnormal vascular development.…”
Section: Discussionmentioning
confidence: 99%